Haji Muhammad Sa’id Bin Jamaluddin Al-Linggi: Amalan dan Sumbangannya dalam Perkembangan Tarekat Ahmadiyyah di Malaysia - Saari, Che Zarrina (Jurnal Usuluddin, 2002)
This article attempts to gather information about Haji Muhammad Sa’id bin Jamaluddin al-Linggi who was known as Sufi in Malay world. He played a vital role in introducing and developing the Ahmadiyyah Order in Negeri Sembilan, Kelantan and several other places.